Pengaruh Terapi Relaksasi Progresif terhadap Penurunan Tingkat Kecemasan dalam Menghadapi Uji Kompetensi Mahasiswa Tingkat III Akper Muhammadiyah Cirebon - Hidayat, Eyet (Jurnal Keperawatan Soedirman, 2017)
A nurse is deemed competent to have a competency certificate obtained through a competency test. Anggraeni Novi (2013): 3rd grader D III Nursing Universitas Pendidikan Indonesia 56% experience anxiety from mild to moderate level in facing competency test. There is an effect of progressive muscle relaxation on anxiety levels in schizophrenic patients in RSJ Bali Province (Laksmi, 2015). This study aims to determine the effect of progressive relaxation therapy to decrease the level of anxiety in the face of nurse competence test at the level III student AKPER Muhammadiyah Cirebon. The study design used "Quasi Experimental Pre-Post Test with Control Group" with progressive relaxation therapy intervention. Population were all students at level III AKPER Muhammadiyah Cirebon with a sample of 72 people. The data collection tool used is an anxiety HARS rating scale (Hamilton Anxiety Rating Scale) measurement questionnaire. The analysis of research results consisted of univariate and bivariate analysis, using percentage, test of t-test and independent t-test. Results: There was a significant decrease in anxiety levels in the intervention group after progressive relaxation therapy (p 0.000). Advice: Progressive relaxation therapy may be applied to decrease anxiety levels among students in the face of competency tests.